PENGARUH PROFITABILITAS TERHADAP NILAI PERUSAHAAN: Studi Empiris Pada Perusahaan Lq45 Yang Terdaftar Di Bursa Efek Indonesia Periode 2015-2019 - Amalia, Nanda Rizki; Nupi Hasyim, Muhamad Ardi (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2021)
Firm value a very important role for the firm. If a firm value is high it will befollowed by high prosperity for its stockholders. Firm value also reflects theinvestor's evaluation of the success of a firm and it is often related to theincrease in the stock exchange price. Maximizing the value of the company isstrongly influenced by sources external or internal company funds. The firmvalue may be explained by firm profitability. High profitability shows a goodprospect of the firm so that investors will positively respond by increasing thestock price and the firm value. So, this research aims to prove the effect of profitability on price book value as a measurer of a firm value in the companieson the Indonesia Stock Exchange in the period of 2015-2019.The samplingtechnique in this research used nonprobability sampling (purposive sampling)with a total sample of 24 companies. The secondary data collection techniquein this research is a literature study. Multiple linear regression is a method usedto analyze the data in this research. The results of this research indicate thatthe partial test (t-test) on the variable profitability proxied by return on equityhas a positive and significant effect on price book value. Profitability, which isproxied by return on assets, has a positive and significant effect on price bookvalue. Meanwhile, for the simultaneous test (f test) profitability has a positiveand significant effect on price book value.